2020
DOI: 10.1111/bjet.12949
|View full text |Cite
|
Sign up to set email alerts
|

What makes learners a good fit for hybrid learning? Learning competences as predictors of experience and satisfaction in hybrid learning space

Abstract: Compared with fully face‐to‐face or online learning environments, implementation of hybrid learning spaces is costly given the spaces making all learning options available for learners. Therefore, decisions on investments in hybrid learning are critical for institutions. Satisfaction and experience of learners is one of the important indicators for assessing the cost‐effectiveness of learning space implementation; thus, predictions of learners' satisfaction and experience can inform institutions' decision maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 36 publications
0
35
0
2
Order By: Relevance
“…Considering the existence of future public health and safety concerns, this and similar scale studies are deemed necessary in education. As a matter of fact, multi-dimensional planning is needed to create both distance education and a hybrid learning environment efficiently (Xiao et al, 2020). Therefore, all education stakeholders should be taken into account with their needs (Koruyucu & Kabak, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the existence of future public health and safety concerns, this and similar scale studies are deemed necessary in education. As a matter of fact, multi-dimensional planning is needed to create both distance education and a hybrid learning environment efficiently (Xiao et al, 2020). Therefore, all education stakeholders should be taken into account with their needs (Koruyucu & Kabak, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Online learning tools help in establishing an effortless interaction between authentic and digital learning resources and at the same time offer personalised learning opportunities. Compared to fully face-to-face learning, e-learning involves lower educational costs and is considered to be more effective and time-saving [20,25]. Positive impacts could be seen in terms of usefulness and student satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…They lack an understanding of the limitations and weaknesses of e-learning, and some may have unreasonable expectations [20]. The students' expectations towards hybrid learning as well as satisfaction prediction are also rarely investigated [25]. Several studies have been carried out on the effectiveness of the use of an online learning environment [36,37], but students' attitude towards interferences with this use have been underresearched.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao et al . (2020) add a practical model for practitioners to realize a hybrid learning space that has a high level of flexibility in terms of time, space and pace of learning. They showed that cognitive engagement competence was significantly associated with hybrid learners' satisfaction and experience.…”
mentioning
confidence: 99%